1981
DOI: 10.1007/bf01320790
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stability of foot-and-mouth disease virus

Abstract: The thermal stabilities of 146S component of seven strains of foot-and-mouth disease virus were found to differ considerably. Inactivation of infectivity with acetylethyleneimine (AEI) reduced the thermal stabilities of all but one of the viruses. Treatment of AEI inactivated and control virus preparations with glutaraldehyde stabilized 146S particles to a considerable extent, whereas treatment with dimethyl suberimidate was less effective. In similar experiments with 75S, natural empty particles, the thermal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
84
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(92 citation statements)
references
References 15 publications
8
84
0
Order By: Relevance
“…Comparison of the kinetics of the FMDV-specific antibody response of experiment 1 and 2 animals over time did not reveal any statistically significant differences between the depleted groups and the control MAb-treated groups. Specific IgM was detected from 4 days postinfection, and specific IgG1 and IgG2 were detected from 5 days postinfection, consistent with reports by other investigators (14,21,58). Our results show that in vivo, in a natural ruminant host, FMDV infection can induce not only a specific and rapid IgM response but also efficient and rapid isotype class switching in the absence of CD4 ϩ T cells.…”
Section: Discussionsupporting
confidence: 92%
“…Comparison of the kinetics of the FMDV-specific antibody response of experiment 1 and 2 animals over time did not reveal any statistically significant differences between the depleted groups and the control MAb-treated groups. Specific IgM was detected from 4 days postinfection, and specific IgG1 and IgG2 were detected from 5 days postinfection, consistent with reports by other investigators (14,21,58). Our results show that in vivo, in a natural ruminant host, FMDV infection can induce not only a specific and rapid IgM response but also efficient and rapid isotype class switching in the absence of CD4 ϩ T cells.…”
Section: Discussionsupporting
confidence: 92%
“…Virion stability is of importance during the vaccine manufacturing process as the maintenance of intact 146S particles is relevant to the amount of immunogenicity induced by antigens and to vaccine efficacy (Doel & Baccarini, 1981;Doel, 2003). In the present study, a comparable decrease in infectivity was observed for the respective viruses at room temperature and above.…”
Section: Custom-engineered Chimeric Vaccine For Fmdsupporting
confidence: 64%
“…Antigen yield is determined by the biophysical properties of FMDV Biophysical stability of the infectious virus or antigen has been correlated with the protective nature of FMD vaccines (Doel & Baccarini, 1981). With this in mind, vKNP/SAT2 and KNP/196/91 were compared in terms of their biophysical properties following treatment at different temperatures, pH values and salt concentrations (Fig.…”
Section: Parental Viral Properties Are Retained In the Recovered Vknpmentioning
confidence: 99%
“…The antigens were checked by standard VP1 sequencing (25). The 146S antigen concentration was determined by quantitative sucrose density gradient analysis, as previously described (26,27). A known 146S FMDV antigen reference standard was tested with each run.…”
Section: Methodsmentioning
confidence: 99%